PENGELOLAAN ALOKASI DANA DESA (ADD) DI DESA ULAK PATIAN KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU TAHUN 2016-2017 - Putra, Satrio Astar Adi; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is a Government Science research that is in the realm of the Village Government System Study Field. The Village Fund is fully managed, in accordance with the laws and regulations, efficient, economical, effective, transparent and responsible by paying attention to a sense of justice and fulfilling and fulfilling the interests of the community. This research is important to provide an overview of Village Fund Management in the context of development both for physical development in this case, facilities and infrastructure as well as community empowerment in the village, especially in Ulak Patian, Kepenuh District, Rokan Hulu Regency. Planning, Implementation, Disbursement, Reporting and Control, Coaching, and Supervision. The management of ADD conducted by the District Government of Ulak Patian Village has fulfilled the technical regulations stipulated in the laws and regulations. But the process is still not optimal. This can be seen from the reporting and disbursement that corrects the delay. For the Realization Reporting process the use of ADD has not been in accordance with the predetermined schedule causing delays in disbursement. Likewise with the responsible responsibility for the use of ADD, the community cannot produce the work of the village government and accountability to local governments that do not carry out on time. Factors that influence the management of Village Fund Allocation in Ulak Patian Village add the quality of the Human Resources of the Village Government Apparatus in the District of Ulak Patian in Kepenuh which have an average high school / high school and junior high school education.Keywords: Management, Allocation, Village Funds